Evaluation of the Efficacy of Stem Cell Therapy in Animal Models of Intervertebral Disc Degeneration Based on Imaging Indicators: A Systematic Review and Meta-Analysis - Wenhao Li; He Zhao; Zhencheng Xiong; Chuanhong Li; Jianbin Guan; Tao Liu; Yongdong Yang; Xing Yu (Hindawi Limited, 2022)
Objective. The purpose of this study is to make a systematic review of the therapeutic effect of stem cells in animal models of disc degeneration from an imaging point of view. Methods. Data were extracted by searching electronic databases for RCTs that met the inclusion criteria. Data analysis was performed using RevMan 5.3 and STATA 15.1 software. This meta-analysis was registered with INPLASY, registration number INPLASY202240148. Results. A total of 34 studies were included, covering four species of animals, rabbits, sheep, rats, and mice, with a total of 1163 intervertebral discs. In terms of DHI, the efficacy of stem cell group in rabbits (P<0.001), mice (P<0.001), sheep (P<0.001), and rats (P=0.001) was better than that in control group. In terms of disc height, the efficacy of stem cell group in rats (P<0.001) was better than that in control group, while in sheep (P=0.355), there was no statistical difference between two groups. In terms of MRI index, the efficacy of stem cell group in rats (P<0.001), mice (P<0.001), and rabbits (P=0.016) was better than that in control group. In terms of MRI signal score, the efficacy of stem cell group in rabbits (P<0.001) was better than that of control group. In terms of T2 signal intensity, stem cell group was more effective than control group in rabbits (P<0.001), mice (P<0.001), and rats (P=0.003).Conclusion. Stem cell therapy can improve intervertebral disc-related imaging parameters in animal models of disc degeneration, indicating that stem cell therapy has a repairing effect on intervertebral discs. However, given the heterogeneity and limitations of this study, this conclusion still needs to be tested by a large number of studies.